2022
DOI: 10.3389/fpubh.2022.854468
|View full text |Cite
|
Sign up to set email alerts
|

Dog and Cat Contact as Risk Factor for Human Toxocariasis: Systematic Review and Meta-Analysis

Abstract: Toxocariasis, a neglected parasitic zoonosis with worldwide distribution, has been reportedly associated to different risk factors in several epidemiological and meta-analysis studies. However, dog and cat contact (environmental and animal exposure) as isolated associated risk factor for children and adults remains to be fully established. Accordingly, the present meta-analysis has aimed to directly assess dog and cat contact for toxocariasis seropositivity in under-18 and adult persons, using a survey strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Our findings showed that the seroprevalence was higher in patients who had a dog in the household. This is consistent with the results of a systematic review in the Americas, Middle East, and Western Pacific Region, which found a statistically significant association between seropositivity for Toxocara and contact with pets, although only in younger people with both dogs and cats ( 132 ). Toxocariasis has a fecal–oral route of transmission where domestic dogs accounted for 39% of the total egg production, followed by feral cats, domestic cats, and foxes ( 4 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings showed that the seroprevalence was higher in patients who had a dog in the household. This is consistent with the results of a systematic review in the Americas, Middle East, and Western Pacific Region, which found a statistically significant association between seropositivity for Toxocara and contact with pets, although only in younger people with both dogs and cats ( 132 ). Toxocariasis has a fecal–oral route of transmission where domestic dogs accounted for 39% of the total egg production, followed by feral cats, domestic cats, and foxes ( 4 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, this way of transmission may be underestimated since transmission of Toxocara to humans via food consumption has not been the subject of extensive research [53] and should be further carefully evaluated. Moreover, despite the small number of embryonated eggs that can be found on the host hair of well-cared animals, human contact with contaminated hair of dogs or cats may represent a further way for transmission [60][61][62][63].…”
Section: Epidemiologymentioning
confidence: 99%
“…Additionally, dogs and cats were mostly unleashed, free-roaming, and not dewormed in the studied quilombola communities. As contact with dogs and cats has already been considered another associated risk factor for toxocariasis, mainly in younger people [ 11 , 56 ], companion animal deworming should be always recommended to reduce Toxocara spp. egg shedding into the environment and posterior transmission via soil ingestion to the exposed population [ 57 ].…”
Section: Discussionmentioning
confidence: 99%